Expression pattern conferred by a glutamic acid-rich protein gene promoter in field-grown transgenic cassava (Manihot esculenta Crantz) - Beltrán Giraldo, Jorge Alonso; Prias, M; Al-Babili, S.; Ladino Franco, Y.J.; López, D.; Beyer, Peter; Chavarriaga Aguirre, Paul; Tohme, Joseph M. (Springer, 2010)
A major constraint for incorporating new traits into cassava using biotechnology is the limited list of known/tested promoters that encourage the expression of transgenes in the cassava’s starchy roots. Based on a previous report on the glutamic-acid-rich protein Pt2L4, indicating a preferential expression in roots, we cloned the corresponding gene including promoter sequence. A promoter fragment (CP2; 731 bp) was evaluated for its potential to regulate the expression of the reporter gene GUSPlus in transgenic cassava plants grown in the field. Intense GUS staining was observed in storage roots and vascular stem tissues; less intense staining in leaves; and none in the pith. Consistent with determined mRNA levels of the GUSPlus gene, fluorometric analyses revealed equal activities in root pulp and stems, but 3.5 times less in leaves. In a second approach, the activity of a longer promoter fragment (CP1) including an intrinsic intron was evaluated in carrot plants. CP1 exhibited a pronounced tissue preference, conferring high expression in the secondary phloem and vascular cambium of roots, but six times lower expression levels in leaf vascular tissues. Thus, CP1 and CP2 may be useful tools to improve nutritional and agronomical traits of cassava by genetic engineering. To date, this is the first study presenting field data on the specificity and potential of promoters for transgenic cassava.